Distributed load aware relay selection algorithm for cooperative relay networks. (10th April 2015) - Jiang, Fan; Wang, Benchao; Lu, Guangyue
Cooperative relaying is accepted as a promising solution to achieve high data rates over large areas in the 4G wireless system. This paper presents a two–step distributed load aware relay selection algorithm (LA–RS) for relay–based cooperative networks. According to current user channel conditions as well as the user numbers that relay serves, LA–RS chooses the optimal relay node for each user in a distributed way. More specifically, in the first step each mobile station (MS) constructs relay selection functions for candidate relay node (RN), and selects the appropriate RN accordingly. Furthermore, in the second step RNs also adopt a weighted channel dependent scheduling algorithm for resource allocation, so as to provide a flexible tradeoff between per–user fairness and aggregate throughput in each cell. Simulation results demonstrate that compared with other relay selection schemes, LA–RS achieves load balancing through effective relay selection method, so as to obtain a tradeoff between the system throughput and the user equity.